Ethnic politics in Pakistan.A case study of Khyber Pukhtoonkhwa (KP) - Azra Bibi; Maryam Bibi; Dr. Muhammad Rizwan; Sadaf Butt (Social Science Review Archives, 2025)
Ethnic politics in Pakistan, particularly within the region of Khayber Pakhtunkhwa (KP), is a dynamic and multifaceted phenomenon that demands a comprehensive examination. This research explores ethnic politics in Khayber Pakhtunkhwa (KP), Pakistan, with a focus on its historical, contemporary, and theoretical aspects. It delves into the historical roots, iconic figures like Khan Abdul Ghaffar Khan, the impact of the Soviet-Afghan War and Afghan refugees, and how ethnic politics influences governance structures, public policies, and inter-group dynamics in KP. Using theoretical frameworks, it examines the theoretical foundations of ethnic politics. The study also analyzes how ethnic politics affects governance, public policies, and inter-group dynamics, leading to socioeconomic, political, and cultural consequences. This research contributes to a deeper understanding of the challenges and opportunities in KP and Pakistan's journey towards peace, unity, and development.